Recent Progress in the Development of Fluorometric Chemosensors to Detect Enzymatic Activity - Wei, Tingwen; Wang, Fang; Zhang, Zhijie; Qiang, Jiang; Lv, Jing; Chen, Tiantian; Li, Jia; Chen, Xiaoqiang (Current Medicinal Chemistry, 2019)
Enzymes are a class of macromolecules that function as highly efficient and specific biological catalysts requiring only mild reaction conditions. Enzymes are essential to maintaining life activities, including promoting metabolism and homeostasis, and participating in a variety of physiological functions. Accordingly, enzymatic levels and activity are closely related to the health of the organism, where enzymatic dysfunctions often lead to corresponding diseases in the host. Due to this, diagnosis of certain diseases is based on the levels and activity of certain enzymes. Therefore, rapid real-time and accurate detection of enzymes in situ are important for diagnosis, monitoring, clinical treatment and pathological studies of disease. Fluorescent probes have unique advantages in terms of detecting enzymes, including being simple to use in highly sensitive and selective real-time rapid in-situ noninvasive and highly spatial resolution visual imaging. However, fluorescent probes are most commonly used to detect oxidoreductases, transferases and hydrolases due to the processes and types of enzyme reactions. This paper summarizes the application of fluorescent probes to detect these three types of enzymes over the past five years. In addition, we introduce the mechanisms underlying detection of these enzymes by their corresponding probes.
Keywords: Chemosensor